2007
DOI: 10.1111/j.1472-4642.2007.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification, diversity, and distribution of Chilean Asteraceae: implications for biogeography and conservation

Abstract: This paper provides a synopsis of the Chilean Asteraceae genera according to the most recent classification. Asteraceae is the richest family within the native Chilean flora, with a total of 121 genera and c. 863 species, currently classified in 18 tribes. The genera are distributed along the whole latitudinal gradient in Chile, with a centre of richness at 33°–34° S. Almost one‐third of the genera show small to medium‐small ranges of distribution, while two‐thirds have medium‐large to large latitudinal ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Studies on Antarctic Nothofagaceae (Francis & Hill, 1996) during the Pliocene suggested a low prostrate habit, more similar to shrubs growing today along exposed parts of the treeline on Isla Navarino in southernmost Chile. Nowadays, beech forests in southern South America are restricted to median to high elevations (up to 2000 m) in the southernmost Andes from c. 33°S to the southernmost extremes of Argentina and Chile (McQueen, 1976;Luebert & Pliscoff, 2006;Moreira-Muñoz & Muñoz-Schick, 2007). The reconstruction of the historical biogeography of Lagenophora, as presented here, in the frame of the apparent association of this genus with the southern cool-temperate beech forest, could contribute to our understanding of the spatio-temporal patterns of the austral biota.…”
Section: Trans-tasman Distribution Of Lagenophoramentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on Antarctic Nothofagaceae (Francis & Hill, 1996) during the Pliocene suggested a low prostrate habit, more similar to shrubs growing today along exposed parts of the treeline on Isla Navarino in southernmost Chile. Nowadays, beech forests in southern South America are restricted to median to high elevations (up to 2000 m) in the southernmost Andes from c. 33°S to the southernmost extremes of Argentina and Chile (McQueen, 1976;Luebert & Pliscoff, 2006;Moreira-Muñoz & Muñoz-Schick, 2007). The reconstruction of the historical biogeography of Lagenophora, as presented here, in the frame of the apparent association of this genus with the southern cool-temperate beech forest, could contribute to our understanding of the spatio-temporal patterns of the austral biota.…”
Section: Trans-tasman Distribution Of Lagenophoramentioning
confidence: 99%
“…Notably, only a few genera of Asteraceae occur in Australia, New Zealand and southern South America, occasionally extending to Asia (Allan, 1961;Moreira-Muñoz & Muñoz-Schick, 2007;Ezcurra, Baccala & Wardle, 2008). One such genus is Lagenophora Cass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These diagnostic species are only missing in the plots from the island of Chiloé and from Argentina. Lasthenia kunthii is widespread southwards (Moreira-Muñoz & Muñoz-Schick 2007) and occurs also in ephemeral wetlands in Patagonia (San Martín et al 2013). FIGURA 4.…”
Section: Vegetationmentioning
confidence: 99%
“…Vernal pools offer a habitat to native annuals, many of them endemic in Chile (Arroyo et al 1990). Additionally, many of these annual species belong to mono-specific genera, such as the Asteraceae Blennosperma, Centipeda, Lasthenia, Micropsis and Microseris (Moreira-Muñoz & Muñoz- Schick 2007, Moreira-Muñoz 2011. The distribution and ecology of vernal pool plant species is poorly known (Alvarez et al , 2012b).…”
Section: Introductionmentioning
confidence: 99%